Using the duration of combined sewer overflow events for the calibration of sewer hydrodynamic models. Issue 8 (14th September 2017) - Montserrat, A.; Hofer, T.; Poch, M.; Muschalla, D.; Corominas, Ll.
Abstract: This paper compares two calibration approaches to enhance the ability of hydrodynamic models to describe the performance of combined sewer overflow (CSO) structures. One approach is based on the duration of CSO events (monitored by low-cost sensors) and the other focuses on the overflow volume. Both were applied to the West-Graz catchment model to simulate the discharge from the CSO overflow channel under small, medium and large rain episodes. The methodology includes sensitivity analysis of the model parameters and automatic calibration through optimization. The results revealed that the calibration using the CSO duration led to results similar to those of the approach that used overflow volume, with less than 12% error differences between approaches for medium and large rain episodes.